Selective ablation of the ligament of Marshall attenuates atrial electrical remodeling in a short‐term rapid atrial pacing canine model. (20th June 2018) - Yu, Xiaomei; He, Wenbo; Qin, Zhiliang; Liu, Shan; Ma, Ruisong; Luo, Da; Hu, Huihui; Xie, Jing; He, Bo; Lu, Zhibing; Jiang, Hong
Abstract: Introduction: Cardiac sympathetic activation facilitates atrial electrical remodeling during atrial fibrillation (AF). Selective ablation of the distal part of the ligament of Marshall (LOMLSPV ) could decrease cardiac sympathetic innervation. This study aimed to investigate the effects of LOMLSPV ablation on atrial electrical remodeling in a short‐term rapid atrial pacing (RAP) model. Methods: In 16 anesthetized dogs, 6 hours of RAP (20 Hz, 2 × threshold) was delivered before LOMLSPV ablation (group 1, N = 8) or after (group 2, N = 8). Heart rate variability (HRV), serum norepinephrine (NE), atrial electrophysiological indices were analyzed. Six times of burst pacing (20 Hz, 2 × threshold, lasting for 5 seconds, were performed to induce AF, the number of episodes and the duration of AF were compared. Results: LOMLSPV ablation decreased sympathetic indices of HRV and serum NE. Atrial effective refractory period (ERP) was shortened during RAP in both groups with higher reduction degrees in group 1. In group 1, the shortening of atrial ERP, elevating of ERP dispersion and sum of window of vulnerability (ΣWOV), facilitating of AF induced by RAP were subsequently reversed by LOMLSPV ablation. In group 2, LOMLSPV ablation prolonged atrial ERP, decreased ΣWOV, eliminated AF induction. The subsequent RAP failed to alter these indices. Histological studies showed abundant sympathetic nerve fibers in LOMLSPV . Conclusion: LOMLSPV ablation could inhibit atrial electrical remodeling during short‐term RAP by reducing the cardiac sympathetic activity. LOMLSPV may be a potential target in AF ablation, especially in patients with highly cardiac sympathetic activation or atrial electrical remodeling.